2020
DOI: 10.3389/fmicb.2020.00709
|View full text |Cite
|
Sign up to set email alerts
|

Direct Binding and Regulation by Fur and HapR of the Intermediate Regulator and Virulence Factor Genes Within the ToxR Virulence Regulon in Vibrio cholerae

Abstract: Cholera toxin (CT) and toxin coregulated pilus (TCP, TcpA is the major subunit) are two major virulence factors of Vibrio cholerae, both of which play critical roles in developing severe diarrhea in human. Expression of CT and TCP is under the tight control of the regulatory cascade known as the ToxR virulence regulon, which is composed of three regulators ToxR, TcpP, and ToxT. Besides, their expression is also regulated by the quorum sensing (QS) master regulator HapR and the regulatory protein Fur. Though tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…Motility is an important virulence determinant during the adhesion and invasion stages in many pathogenic bacteria and enables bacterial cells to swim to nutrient-rich niches or avoid environmental stresses ( 46 ). Previous research has suggested that Fur directly activates the transcription of toxin coregulated pilus tcpA, which was necessary for colonization by binding to their promoters in V. cholerae ( 47 ). In Shigella flexneri , Fur could indirectly activate the icsA gene that facilitates bacterial movement by activating VirF ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Motility is an important virulence determinant during the adhesion and invasion stages in many pathogenic bacteria and enables bacterial cells to swim to nutrient-rich niches or avoid environmental stresses ( 46 ). Previous research has suggested that Fur directly activates the transcription of toxin coregulated pilus tcpA, which was necessary for colonization by binding to their promoters in V. cholerae ( 47 ). In Shigella flexneri , Fur could indirectly activate the icsA gene that facilitates bacterial movement by activating VirF ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…ToxT has been shown to directly bind to the promoters of virulence genes in V. cholerae [ 35 , 45 ]. The ToxT protein comprises 276 amino acids and belongs to the AraC/XylS-type transcriptional regulator family [ 13 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a specific CarR-bound sequence (5-TAATGAGAATTACT-3; −186 to −172 from the tcpP translational start site) was confirmed. Previous research showed that several regulators could directly bind to the tcpP promoter, including AphA, AphB, HapR and CRP 47 , 48 . A small RNA (~91 nt), which was named TarA, is also located in the tcpP promoter 49 .…”
Section: Discussionmentioning
confidence: 99%